Does high-stakes testing increase cultural capital among low-income and racial minority students? - Hong, Won-Pyo; Youngs, Peter (Education Policy Analysis Archives, 2008)
This article draws on research from Texas and Chicago to examine whether high-stakes testing enables low-income and racial minority students to acquire cultural capital. While students' performance on state or district tests rose after the implementation of high-stakes testing and accountability policies in Texas and Chicago in the 1990s, several studies indicate that these policies seemed to have had deleterious effects on curriculum, instruction, the percentage of students excluded from the tests, and student dropout rates. As a result, the policies seemed to have had mixed effects on students' opportunities to acquire embodied and institutionalized cultural capital. These findings are consistent with the work of Shepard (2000), Darling-Hammond (2004a), and others who have written of the likely negative repercussions of high-stakes testing and accountability policies.